Secondhand learning from graduates of leadership development programs. Issue 8 (7th October 2014) - F. Goldman, Ellen; Wesner, Marilyn; M. Plack, Margaret; N. Manikoth, Nisha; Haywood, Yolanda
Abstract : Purpose: – This paper aims to explore the impact leadership development program graduates had on their workgroup, the nature of that impact and how that impact occurred. Design/methodology/approach: – This research was conducted at three sites using a qualitative interview methodology with thematic data analysis. Techniques to ensure trustworthiness included purposive sampling, triangulation of researchers, member checks and code checking. Findings: – Analysis of the data revealed secondhand learning as specific changes in practices, behaviors and attitudes, transferred by program graduates to their peers and supervisors. The transfer of learning was described as both intentional and informal learning during episodes of varying duration, and occurred through a variety of dyadic and group interactions in a manner generally consistent with the 4I framework of organizational learning. Research limitations/implications: – The study was limited to medical educators. Recommendations for supervisors and organizations to maximize training transfer are identified. These suggestions advocate for actively encouraging graduates in departmental leadership and faculty development; focusing transfer on specific practices, behaviors and attitudes; and considering both short- and long-term outcomes. Originality/value: – This paper makes an original contribution to the literature by describing the process of secondhand learning from leadership development program graduates. The paper also expands our understanding of the nuances in transfer methods and associated learning episodes in the context of an educational environment. Finally, the research illustrates how qualitative methods can be used to expose secondhand learning.